Insect Larval Meal as A Possible Alternative to Fish Meal in Rainbow Trout (Oncorhynchus mykiss) Diets: Black Soldier Fly (Hermetia illucens), Mealworm (Tenebrio molitor) - Uslu, Ali Atilla; Ozel, Osman Tolga; Örnekci, Gürel Nedim; Çelik, Burcu; Çankırılıgil, Ekrem Cem; Coskun, Isa; Senel, Gulsad Uslu (My University, 2023)
This study was conducted to determine the effect on growth performance and intestinal histomorphology of the rainbow trout (Oncorhynchus mykiss) fed diets including black soldier fly (Hermetia illucens) prepupae meal (HI) and mealworm (Tenebrio molitor) larvae meal (TM) used instead of fish meal. Six diets with HI and TM at three inclusion levels (10%, 20% and 30%) and a control diet based on fish meal were prepared. Test diets were encoded as control, HI10, HI20, HI30, TM10, TM20 and TM30. Fish (average initial weight of 34.17±0.88 g) were randomly placed (30 for each) in 500 L fibreglass tanks. Each of the seven diet treatments was tested in triplicated tanks. Fish were fed by hand at a level of 2.5% of body weight three times a day for 90 days. Results demonstrated that the growth performance and intestinal histomorphology were significantly affected by black soldier fly (HI) prepupae meal substitution (p<0.05). HI prepupae meal used instead of the fish meal had a negative effect on the growth performance, but not on the intestinal villi length. In addition, intestinal villi width decreased in fish on diets containing 10% or 20% HI prepupae meal. The growth performance and intestinal histomorphology were significantly affected by diets including TM. The diets containing 20% and 30% TM meal significantly decreased growth performance variables, but intestinal villi length increased. The results suggest that mealworm meal (10%) can be included in diets of rainbow trout at a level of 10% instead of fish meal without adversely affecting growth performance. Future studies should be expanded using a highly defatted TM and HI larvae meals.
Keywords: Villus; Aquaculture; nutrition; growth; trout